PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA KELAS VIIIB SMPN 14 MADIUN - Ervinda Ika Nur Aysah; Sardulo Gembong; Lilik Sulistyawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the effectiveness of implementing the Culturally Responsive Teaching (CRT) approach in improving student learning outcomes. The method used is classroom action research (CAR), conducted during the Field Experience Program (PPL) in class VIIIB at SMPN 14 Madiun. Data collection was carried out through tests, documentation, and observation. Data analysis included both quantitative and qualitative data, with research instruments consisting of test sheets, including pre-tests and post-tests. The results showed that student learning outcomes, particularly in the area of knowledge, significantly improved from 57% in Cycle I to 83% in Cycle II. These findings demonstrate that the implementation of the Culturally Responsive Teaching (CRT) approach is effective in enhancing student learning outcomes.